Le Turak, théâtre visuel et musical ou de l’objet à la poésie musicale (Itinera, 2017)
The Turak Théâtre d’objets is a company which was created by Michel Laubu thirty years ago. Their objective is to turn each spectator into a child again. In order to reach that goal, why not use poetry and imagination? Their work consists in transforming the objects you use everyday: they may be turned into characters, pieces of furniture or musical instruments: for instance you might find drums made of barrels, or the invention of an instrument, the « arsenoïtal », or the creation of a clarinet, etc... We can highlight the link between the objects and the music in the shows by the Turak company so as to show how the relation between seeing, touching and hearing leads to musical poetry.